CRACK RESISTANCE OF REINFORCED CONCRETE STRUCTURES OF RING SECTIONS - Nikolay N. Trekin; N. Kodysh; Sergey G. Parfenov; Konstantin R. Andrian (Journal of Mechanics of Continua and Mathematical Sciences)
In this paper, the issues of developing a calculation method for the formation of cracks normal to the longitudinal axis of bent reinforced concrete structures of circular cross-section without prestressing the reinforcement based on a nonlinear deformation model using a bilinear diagram of the state of concrete are considered. The prerequisites based on which theoretical dependences are constructed to determine the complex internal forces of a round normal section before the formation of cracks is presented. Based on stereometry, dependencies are presented to determine the forces in the concrete and reinforcement of the compressed zone and the forces in the stretched zone, respectively, for concrete and reinforcement. Since it is difficult to analytically solve a system of equations with negative and positive exponents, it is recommended to carry out numerical iterative processes to determine the desired unknowns: heights of the compressed zone, maximum stresses in concrete and reinforcement of the compressed zone. Numerical studies have made it possible to determine the value of the elastic-plastic moment of the annular section and to identify its dependence on the strength of concrete.